Analysis of rectifying behavior of novel ball-type binuclear phthalocyanine based devices - Yazici, Aysegul; Ozkan, Ceyda; Gezer, M. Birkan; Altindal, Ahmet; Salih, Bekir; Bekaroglu, Ozer (ELSEVIER SCIENCE SA, 2013)
A new mono substituted derivatives 1 and 2 were prepared by a nucleophilic displacement reaction of 4-nitrophthalonitrile with pyridine-2,6-dimethylol. Novel metallophthalocyanines 3-4 (M = Zn, Co respectively), and ball-type binuclear phthalocyanines 5-6 with four peripheral pyridine-2,6-dimethyloxy groups were synthesized by cyclotetramerization of the phthalonitrile and characterized by elemental analyses, FT-IR, H-1 NMR, UV-Vis and MALDI-TOF MS spectral data. The effects of molecular structure on the charge transport properties of novel metallophthalocyanines 3-4 and ball-type binuclear phthalocyanines 5-6 with four peripheral pyridine-2,6-dimethyloxy groups based devices are investigated using I-V measurements. From our study, we found that ball type films showed an enhanced mobility of nearly ten times that of typical mono Pcs. At low voltages (V 1V) levels the conduction is dominated by space charged limited conduction (SCLC) with exponential distribution of trapping levels. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Mobility; Space charge limited conductivity; Phthalocyanine; Rectifying; GAS-SENSING PROPERTIES; ELECTRICAL-PROPERTIES; THIN-FILMS; ELECTROCATALYTIC PROPERTIES; ZINC-PHTHALOCYANINE; CONDUCTION; UNITS; ELECTRODES; TRIAZINE; COPPER; Chemistry